Transmasculinidades, direitos sexuais e reprodutivos e representações sociais - Pierry, Larissa Goya (2023)
Transmasculinities are a category part of the umbrella term of trans identities, whose experience is marked by transgenderity, that is, the non-agreement between sex and gender, encompassing a series of identities and/or expressions of gender that escape cisgenderity. Transmasculinities remain a relatively recent and invisible political category within the LGBTTQIA+ movement, which impacts on the guarantee and execution of their rights, including sexual and reproductive rights (SRR). Since this is a non-homogeneous group, it is possible to point out that trans men access parenthood in different ways, and some, even after transition, wish to access it through pregnancy, which generates a complex experience that challenges sex/gender constructs. Considering that pregnancy and reproduction are experiences associated with the feminine and the body of cis women, we question: What discourses does the media spread about pregnancy and parenting for trans men? How are these discourses associated with representations of femininity and masculinity? And, in what ways does the medicalization and pathologization of trans identities make other aspects of trans men's lives invisible? Therefore, when we consider the media as important spaces for (re)construction and dissemination of social representations, our general objective is to analyze the possible meanings attributed to the parenting and gestation by trans men in the media. As specific objectives, to identify how and which social representations of masculinities and femininities are involved in this mediatization of trans men who gestate and to discuss in what ways the medicalization and pathologization of transmasculinities impacts on the execution of their sexual and reproductive rights. To this end, we intend to carry out a content analysis of the documentary "Pregnant Father" (2022). As theoretical references, we have the Theory of Social Representations (TSR) and Transfeminism. We realize that there can be an invisibility of pregnancy and parenting of trans men when they are framed within an idea of “symbolic sterilization”, as if trans people did not want or could not generate a life or constitute families, configuring as “unthinkable parenting”. We conclude that the neglect of the sexual and reproductive rights of the trans population is directly related to the medicalization and pathologization of their identities, as well as the reduction of their experiences to hormonal transition and surgical procedures, based on the myth of the “true transsexual”, as well as we have noticed the importance of disseminating narratives and life stories of trans people in the media as a form of humanization and representativeness. From this, it becomes important to denaturalize representations about gender, to consider trans pregnant men in their specificities, ensuring their right to reproduction and parenting.